PUBLIC SECURITY – OBJECT OF POLICE PROTECTION - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2016)
The analysis of the notion ‘public security’ reveals its two parts: 1) conditions where there is no threat to an individual, society or state; 2) measures by the state that ensure these conditions and instills in people the sense of security. These elements to a certain extent determine the features and characterize public security as an object of police protection and as a definition of the notion. Public security is based on two elements: 1) public peace when there is peace, cooperation and confidence in safety in the public realm; 2) conditions of protects ability where the state (the police) continuously provides public security and is ready to render help and neutralize any threats. Thereby in the legal reality public security is police legal relations where the subjects are, on the one hand persons, society, state institutions that have a constant need of protection against crimes and other offences and, on the other hand, the state whose task is to ensure the protection stated in the legislation via competent institutions.